2020
DOI: 10.1089/ten.tea.2019.0188
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Ciliary Functionality of Different Airway Epithelial Cell Lines in Three-Dimensional Cell Culture

Abstract: Three-dimensional respiratory tissue models have been generated using, for example, human primary airway epithelial cells (hAEC) or respective cell lines. To investigate ciliopathies, such as primary ciliary dyskinesia, the presence of functional kinocilia in vitro is an essential prerequisite. Since access to hAEC of healthy donors is limited, we aimed to identify a respiratory epithelial cell line that is capable to display functional kinocilia on at least 60% of the apical surface. Thus, we cultured four di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 29 publications
2
39
1
1
Order By: Relevance
“…It was previously found that after silica nanoparticle exposition, HBEC3-KT secreted significantly lower concentrations of IL-6 compared to the respiratory cell line BEAS-2B. 24 We found in our previous study 9 that another part of the innate immune system, the differentiation to the mucociliary phenotype, was impaired in HBEC3-KT. Thus, we assume that HBEC3-KT are not suitable to study the impact of CyaA further, since the innate immune response, at least in terms of IL-6 secretion and mucociliary differentiation, differs from observations made in primary respiratory epithelial cells.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…It was previously found that after silica nanoparticle exposition, HBEC3-KT secreted significantly lower concentrations of IL-6 compared to the respiratory cell line BEAS-2B. 24 We found in our previous study 9 that another part of the innate immune system, the differentiation to the mucociliary phenotype, was impaired in HBEC3-KT. Thus, we assume that HBEC3-KT are not suitable to study the impact of CyaA further, since the innate immune response, at least in terms of IL-6 secretion and mucociliary differentiation, differs from observations made in primary respiratory epithelial cells.…”
Section: Discussionmentioning
confidence: 59%
“…As a 3D scaffold for tissue model generation, we used decellularized segments of the porcine small intestinal submucosa (SIS), as described elsewhere. 9,14,15 Animal research was performed according to the German law and institutional guidelines approved by the Ethics Committee of the District of Unterfranken, Wu¨rzburg, Germany (approval number: 55.2-2532-2-256). SIS segments were fixed between two cylinders.…”
Section: D Nasal Mucosa Tissue Model Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Limitations of the in vivo (mainly linked to animal experimentation and species specificity) and in vitro (especially morphological and functional variations in non-differentiated versus differentiated cells, respectively) models were overcome thanks to the use of three-dimensional in vitro tissues reconstituted from primary cells. Such ex vivo models are morphologically and functionally close to the airway epithelium and constitute the most suitable approach to study human viral respiratory infections [ 21 , 22 ]. During the 21st century, more 3D culture models, such as rotating wall vessel (RWV) and NASA 3D systems, have also been extensively used as an appropriate surrogate model to recapitulate the 3D architecture and the multicellular complexity of tissues observed in vivo and study virus-host interaction including RSV [ 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the features of 3D culture cells are closer to the complex in vivo condition 6 . Some researchers found that 3D cell cultures could induce pluripotent stem cells (iPSC) to generate personalized tissue models 7 . As the dermal papilla cells (DPCs) are unique mesenchymal cells, we previously found out that DPCs could also induce human hair growth in mice by transplanting intact DPCs and epithelial cells 4,8 .…”
Section: Introductionmentioning
confidence: 99%